Asian Infrastructure Investment Bank as A Platform for China's Power Expansion - Fikram Rettob (Syntax Corporation, 2022)
China has known as a new rival of the United States of Amerika which has good economic growth. China tries to be a new superpower country in the world, it can be seen since the 1940s when China expands its economy' power to others. But, the goal of China was unsuccessful because of the power of the USA in an economy that hegemony the international institution such Bretton Wood, that goal of China widely spreads when China established the Asia Infrastructure Investment Bank which can be used to challenge Bretton Wood institutions. The aims of this journal to analyze the hegemony and the interest of China behinds the establishing of AIIB, and the aim of AIIB itself. To understand this case deeply, the writer is using dependency theory by Dos Santos which explained the international economic system that only brings benefits for those who had the capital. And this paper is using a descriptive qualitative method which based on secondary data such collecting data from books, journal, and validity news that can be helped